Evaluation of System Response Time in RFID-Enabled Mobile Applications for Managing Infectious Disease Patients: A Solution for Pandemic Outbreaks - Sudarma, Made; Sri Ariyani, Ni Wayan; Suartha, I. Nyoman; Udayana, I. Putu Agus Eka Darma (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The global pandemic has changed the paradigm for treating infectious disease patients. This study aims to evaluate the response speed of a mobile application system integrated with RFID technology to assist nurses in monitoring inpatients with infectious diseases in hospitals. When a patient presses the emergency button on the mobile application, this will trigger an API call to retrieve the patient’s location data based on their RFID tag before notifying the nurse through the hospital management system. Testing was carried out on API response times using Android devices with OS versions 8, 10, and 13. Test results showed optimal response times under 2 seconds on average for all versions, with the fastest time of 1.081 seconds on Android 10. Analysis indicated Android 10 had the lowest lag, while Android 13 saw increased lag, likely due to more complex software. These findings suggest that RFID integration with mobile applications can enable rapid emergency response, where system optimization is critical for efficiency.